ETHICAL FRAMEWORK, CULTURAL HUMILITY IN FOSTERING INNOVATION IN CLINICAL PSYCHOLOGY - Jibrin, Ahmed; Sammni, Nuhu Gideon; Muhammed, Tanimu (African Journal of Social and Behavioural Sciences, 2025)
This paper advances an integrative ethical framework for clinical psychology that aligns mid-level Principlism with cultural humility to guide decisions in culturally plural, innovation-driven care settings. We address a practical problem: clinicians must weigh autonomy, beneficence, non-maleficence, and justice while engaging patients’ cultural values and fast emerging technologies. The aim is to provide a concise, actionable model that clarifies how Principlism can be operationalized without erasing local meanings of illness, care, and community. Drawing on illustrative cases, digital mental-health tools, eco-conscious nanomedical approaches, traditional herbal practices, and a subnational vignette from Keffi, Nasarawa State, we show how cultural humility calibrates principle-based analysis, improving consent processes, risk appraisal, and fairness in access. The contribution is a pragmatic ethical framework for clinical psychology that specifies when and how to adapt principled reasoning to context while preserving normative rigor. Implications include transparent justification of clinical choices, culturally responsive consent and disclosure, and criteria for selecting and evaluating innovations so that interventions remain equitable, respectful, and clinically defensible across diverse populations.